Perencanaan Dinding Penahan Tanah Di Ruas Jalan Desa Tanjung Pakis Aji Jepara - Faizah, Nur Laili; Umam, Khotibul; Rochmanto, Decky; Ariyanto (Jurnal Civil Engineering Study, 2024)
Retaining walls are a ground control technique that is very necessary to overcome landslides. As happened in the Tanjung Pakis Aji village area. It has steep slopes and there are indications that landslides often occur during the rainy season. The soil parameters that need to be known to plan soil retention walls for testing include specific gravity (Gs); 2.65 kN/m2, void number (e); 33.9, porosity 97.14, shear angle φ ; 29.71 ˚, soil cohesion (c) 24.5 kN/m2, dry soil volume weight (yd ) ; 1.18 kN/m3, wet soil volume weight (yb); 1.87 kN/m3, air content (Wn); 15.29%. Dimensional calculations, stability control, reinforcement of retaining walls are very important in planning retaining walls. The aim of this research is to plan a retaining wall at this location using a cantilever type retaining wall. The results show that the cantilever type retaining wall with dimensions H = 7 m, B = 3 m, T = 0.4 m, Tt and Th = 0.5, Lt = 1, Lh = 1.m, the cantilever is declared safe for the condition of the soil with a safety factor value of Fgs = 4.061 (safe), Fgl = 2.57 (safe), F carrying capacity = 6.62 (safe). From these calculations, reinforcement of types D19-250, D19-200, D19-200 can be obtained, with shrinkage reinforcement D13-100, D13-200.